Μ-Opioid Activity in Chronic TMD Pain Is Associated with COMT Polymorphism. (November 2019) - Nascimento, T.D.; Yang, N.; Salman, D.; Jassar, H.; Kaciroti, N.; Bellile, E.; Danciu, T.; Koeppe, R.; Stohler, C.; Zubieta, J.K.; Ellingrod, V.; DaSilva, A.F.
Clinicians have the dilemma of prescribing opioid or nonopioid analgesics to chronic pain patients; however, the impact of pain on our endogenous µ-opioid system and how our genetic profile (specifically catechol-O-methyltransferase [ COMT ] polymorphisms) impacts its activation are currently unknown. Twelve chronic temporomandibular disorder (TMD) patients and 12 healthy controls (HCs) were scanned using positron emission tomography (PET) with [ 11 C]carfentanil, a selective radioligand for µ-opioid receptors (µORs). The first 45 min of each PET measured the µOR nondisplaceable binding potential (BPND ) at resting state, and the last 45 min consisted of a 20-min masseteric pain challenge with an injection of 5% hypertonic saline. Participants were also genotyped for different COMT alleles. There were no group differences in µOR BPND at resting state (early phase). However, during the masseteric pain challenge (late phase), TMD patients exhibited significant reductions in µOR BPND (decreased [ 11 C]carfentanil binding) in the contralateral parahippocampus ( P = 0.002) compared to HCs. The µOR BPND was also significantly lower in TMD patients with longer pain chronicity ( P < 0.001). When considering COMT genotype and chronic pain suffering, TMD patients with the COMT 158 Met substitution had higher pain sensitivity and longer pain chronicity with a 5-y threshold for µOR BPND changes to occur in the parahippocampus. Together, the TMD diagnosis, COMT 158 Met substitution, and pain chronicity explained 52% of µOR BPND variance in the parahippocampus (cumulative R 2 = 52%, P < 0.003, and HC vs. TMD Cohen's effect size d = 1.33 SD). There is strong evidence of dysregulation of our main analgesic and limbic systems in chronic TMD pain. The data also support precision medicine by helping identify TMD patients who may be more susceptible to chronic pain sensitivity and opioid dysfunction based on their genetic profile.